Studying the use of mathematics in economic sciences between verbal logic and mathematical analysis - FARHI, Mohamed (Social Sciences Journal)
Our research paper is concerned with identifying the uses of mathematics in economic sciences between verbal logic and mathematical analysis through two groups of economic thinkers. From this point of view, we are trying to stand on the necessity that the economy really needs mathematics to express and explain its phenomena, but with specific amounts and a specific methodology.